ANALISIS IMPLEMENTASI PROGRAM PELATIHAN SUMBER DAYA MANUSIA DI BPJS KESEHATAN CABANG KOTA SEMARANG - Diva Mahendra, Caesar; Hanani, Retna; Zarkasyi Rahman, Amni (Journal of Public Policy and Management Review, 2024)
Human Resources Training plays a crucial role in improving employee skills and expertise that can have a positive impact on the overall performance of the organization, especially for employees of the Semarang City Branch of BPJS Kesehatan. The training program was carried out in order to improve the quality of work of employees, but there were still several complaints regarding the declining quality of work of employees of the Semarang City Branch of BPJS Kesehatan. The purpose of this study was to determine and analyze the training program at the Semarang City Branch of BPJS Kesehatan and the factors that influence the training program. This study used a descriptive qualitative method with data collection techniques in the form of interviews and literature studies. The results of the study showed that the Human Resources training program at the Semarang City Branch of BPJS Kesehatan had been running quite well, but there were still several dimensions that were not optimal. Supporting factors that influenced the Human Resources training program at the Semarang City Branch of BPJS Kesehatan were top management support, commitment of specialists and generalists, organizational complexity, and learning styles. Meanwhile, the inhibiting factors that influenced were technological advances.